Kemampuan Translasi Representasi Siswa pada Materi Aljabar Berdasarkan Tingkat Kemampuan Matematis Kelas VIII MTs PSM Tanen - Ula, Vivi Ni’matul; Hadi, Syaiful (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
Representation has various forms in conveying ideas, such as symbols, verbal, graphs, and tables. In changing from the source representation to the requested target representation, students must have representational translation skills, especially in algebra. Representational translation ability is important for students because it can prevent misunderstanding in solving math problems and help understanding algebra material. This study aims to describe the representational translation ability of students with different levels of mathematical ability in the algebra material of class VIII MTs PSM Tanen. The results showed that students with high mathematical ability were able to fulfill most of the indicators for representational translation from verbal form to symbolic form (V-S), but not fully on the translation from symbolic to verbal form (S-V). Students with moderate mathematical ability can fulfill most of the V-S indicators, but have limitations in S-V. Meanwhile, students with low mathematics ability were not able to fulfill the V-S or S-V indicators. In conclusion, representational translation ability varies between students with high, medium, and low mathematics ability. Students need to be helped to improve this translational ability in order to understand and solve math problems better, especially in algebra material.